Motivasi Belajar dan Lingkungan Keluarga Terhadap Hasil Belajar Siswa Kelas XI Mata Pelajaran Ekonomi - Septianingrum, Catur Hirma; Fitrayati, Dhiah (Jurnal Pendidikan Ekonomi (JUPE), 2024)
The research aims to analyze how learning motivation and family environment partially or simultaneously affect the learning outcomes of economic subjects for class XI students of SMA Negeri 1 Tanjunganom Nganjuk. The approach used is quantitative correlation with the subject, namely 144 children of the saturated sample technique. Data were obtained through questionnaires and tests. Data analysis is multiple linear regression. The results showed a significant influence of learning motivation and family environment, partially or simultaneously, on the learning outcomes of economic subjects in class XI SMA Negeri 1 Tanjunganom Nganjuk.